SAT0204 Investigation of fluoroquinolone-induced myalgia using 31p magnetic resonance spectroscopy and in vitro contracture tests. (1st June 2001) - Guis, S; Bendahan, D; Kozak-Ribbens, G; Mattei, JP; Le Fur, Y; Figarella-Branger, D; Jouglard, J; Cozzone, PJ
Abstract : Background: Adverse rheumatological effects of fluoroquinolone treatment such as tendinopathies, arthralgia and myalgia have been reported. The exact mechanism of fluoroquinolone toxicity remains unclear. Objectives: To investigate muscle function in patients suffering from severe myalgia resulting from fluoroquinolone treatment. We used histology, in vitro contracture tests (IVCT) and 31P magnetic resonance spectroscopy (31P MRS) to explore muscular contraction and metabolism. Methods: Three patients were investigated suffering after fluoroquinolone treatment from myalgia, hyperalgia tendinopathy and arthralgia. Control group included nine subjects, all of them were free of any muscle disease. Muscle biopsies were performed on the left biceps, IVCT were performed in accordance with the protocol recommended by European Malignant Hyperpyrexia Group (EMHG). 31P MRS concicted to MR spectra of forearm flexor muscles were recorded at 4.7 T throughout a rest-exercise-recovery protocol. Results: No specific histologic anomalies were observed in muscle biopsies. In vitro contracture tests diagnosed one patient as susceptible to Malignant hyperthermia. 31P MRS detected in all patients a significant reduction of pH magnitude changes measured at end of exercise and a faster rate of proton efflux measured during recovery. Conclusion: Muscle abnormalities described in the present study of three patients after fluoroquinolone treatment clearly pointed out the organicity of fluoroquinolone-induced myalgia. All three patients displayed an aceleration of proton efflux and a limited acidosis likely in relation with changes of transporters involving in the transport of Na+, H+ and Ca 2+ .